Association between Oral Health Status and Diabetic Nephropathy-Related Indices in Japanese Middle-Aged Men. (10th June 2020) - Yoshioka, Masami; Okamoto, Yoshifumi; Murata, Masahiro; Fukui, Makoto; Yanagisawa, Shizuko; Shirayama, Yasuhiko; Nagai, Kojiro; Hinode, Daisuke
Abstract : Oral health status is known to be associated with lifestyle-related diseases such as diabetes and chronic kidney disease. In Japan, around 40% of hemodialysis cases are patients with diabetic nephropathy. The aim of this study was to clarify the association between oral health status and diabetic nephropathy-related indices in Japanese middle-aged men. Sixty-six men (age range: 55–64 years) with ≥20 remaining teeth and who received public medical checkups and oral examinations were enrolled. We examined correlations of age, body mass index, HbA1c, HDL-C, LDL-C, neutral fat, serum creatinine, and the estimated glomerular filtration rate (eGFR) with the number of remaining teeth or the community periodontal index (CPI) score (periodontal pocket < 4 mm : 0, 4–6 mm: 1, ≥6 mm: 2). A positive correlation between the CPI score and serum creatinine and a negative correlation between CPI score and eGFR (Spearman's rank correlation coefficient, r = 0.459, p < 0.01, and r = − 0.460, p < 0.01, respectively) were observed. The mean eGFR in the CPI score 0 group was significantly higher than that in the CPI score 1/2 group (82.6 vs. 70.7, Student's t -test, p < 0.01 ). Logistic regression analysis using eGFR as a dependent variable and age, CPI score, body mass index, HbA1c, and neutral fat as independent variables suggested that low eGFR (<60) could be attributed to CPI score (OR = 3.169, 95% CI: 1.031–9.742, p = 0.044 ). These results suggest a possible association between periodontal status and renal function in Japanese middle-aged men. Periodontal condition is controlled by oral prophylaxis, and periodontal disease and chronic kidney disease have some common risk factors. Thus, periodontal management can contribute to the prevention of severe chronic kidney disease.